The Role of Self-Efficacy in Improving the Academic Achievement of Students in the Faculty of Tarbiyah, Department of PGMI UIN Raden Intan Lampung - Laini Asra Asra (PARADIGMA: JURNAL PEMIKIRAN DAN PENELITIAN PENDIDIKAN, 2025)
This study explores the influence of self-efficacy on the academic achievement of students in the Madrasah Ibtidaiyah Teacher Education (PGMI) Study Program at the Faculty of Tarbiyah. Self-efficacy defined as an individual’s confidence in their ability to perform academic tasks—plays a critical role in shaping students’ motivation, learning strategies, and persistence when facing challenges. Drawing on data from 220 PGMI students, this research utilized the General Self-Efficacy Scale (GSE) alongside official academic records to examine the relationship between perceived competence and performance. The findings reveal a significant positive correlation between self-efficacy and academic achievement. These results underscore the need to strengthen self-efficacy throughout pre-service teacher education by integrating psychologically supportive pedagogy and structured learning environments that foster confidence and autonomy in future educators